Psychological characteristics of the microsocial environment as predictors of remission among patients with depressive and anxiety neurotic disorders - V. V. Bocharov; A. M. Shishkova; E. A. Dubinina; T. A. Karavaeva; D. A. Starunskaya; Yu. S. Chernaya; D. M. Saraykin; A. Yu. Vinnikova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The wide representation among the Russian population of depressive and anxiety disorders, manifested both in the form of independent nosological forms and in the form of comorbid conditions, determines the importance of studying the factors that determine their etiopathogenesis. The patient’ microsocial environment is traditionally considered as a significant predictor, largely determining the course of depressive and anxiety disorders. At the same time, there is a lack of studies revealing the ratio of the psychological content of relatives’ experiences with the severity of symptoms and clinical dynamics of the patient’s condition.The aim of the study was to determine the value of the psychological characteristics of the microsocial environment of patients with depressive and anxiety disorders for predicting the clinical dynamics of their condition during inpatient treatment and in catamnesis (six months after discharge). Based on the investigation of 50 patients (17 men, 33 women, average age 27.81 [SD = 9.96] years) and 50 relatives (16 men, 34 women, average age 48.04 [SD = 11.45] years), it was shown that the nature of the relationship to the disease of a loved one and the perception of family situation by relative are interrelated with indicators reflecting the dynamics of patients’ remission. In particular, emotional support from a loved one contributes to the of the patient’s is improvement at the inpatient treatment phase. And the presence of understandable family rules, orderliness, hierarchical relationships, as well as attention to moral aspects in the family contributes to the stabilizatioin of remission in a delayed perspective.The data obtained indicate the importance of a systematic approach in the psychotherapy of depressive and anxiety disorders, taking into account both the individual psychological characteristics of patients and the characteristics of their microsocial environment.